2016
DOI: 10.1111/ans.13852
|View full text |Cite
|
Sign up to set email alerts
|

Response of an ovine laryngeal injury model to a novel fibrosis inhibitor

Abstract: In an ovine laryngeal injury model, administration of a fibrosis inhibitor resulted in altered elastin and collagen deposition after injury in the glottis. Further investigation is warranted to examine whether these tissue changes affect vocal fold dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(94 reference statements)
1
4
0
Order By: Relevance
“…Changes in the VF secondary to injury were confirmed including reduction of epithelial thickness, reduction in collagen density at 1 month and loss of elastin (matching previously published data in this model) 25 . Both halofuginone and dexamethasone moderated collagen loss but halofuginone treatment was also protective against elastin depletion.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Changes in the VF secondary to injury were confirmed including reduction of epithelial thickness, reduction in collagen density at 1 month and loss of elastin (matching previously published data in this model) 25 . Both halofuginone and dexamethasone moderated collagen loss but halofuginone treatment was also protective against elastin depletion.…”
Section: Discussionsupporting
confidence: 85%
“…Changes in the VF secondary to injury were confirmed including reduction of epithelial thickness, reduction in collagen density at 1 month and loss of elastin (matching previously published data in this model). 25 Both halofuginone and dexamethasone moderated collagen loss but halofuginone treatment was also protective against elastin depletion. In addition, Smad3 binding in both halofuginone and dexamethasone‐treated sheep was significantly less prominent than in triamcinolone‐treated sheep suggesting modulation of the Smad3 fibrotic pathway.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ertugrul et al 16 administered halofuginone topically for 5 minutes in a rat model of subglottic trauma and reported a preventive effect of halofuginone on fibrosis and stenosis. In another study, Allen 26 administered halofuginone orally for 10 weeks and observed a trend toward a decrease in the collagen density after injury in an ovine laryngeal injury model. Halofuginone can be administered orally, intravenously, intraperitoneally, and topically.…”
Section: Discussionmentioning
confidence: 97%
“…This process suppressed type 1A collagen production with minimal effect on other normal collagen subtypes. Allen et al demonstrated that administration of halofuginone resulted in decreased elastin and collagen deposition in acute VF injury using ovine in vivo model [112].…”
Section: New Strategies For Vf Scar Including Regenerative Medicinmentioning
confidence: 99%